The application of international human rights law to unrecognised entities: the case of Taiwan - Tsai, Pei-Lun (2015)
Traditionally, only States are considered as duty-bearers under international human rights law. Fundamental human rights guarantees have been conceived as standards of legal protection for individuals against the abuse of States. However, with the emergence of various non-State actors, States are no longer the only entities who may interfere with the enjoyment of human rights. The obligations of certain categories non-State actors under international human rights law have been much studied, but the application of international human rights law to “unrecognised entities”, who fulfil the traditional criteria of statehood and have achieved de facto independence but are not generally recognised as States by the international community, have received relatively limited scholarly attention. This thesis aims to fill this gap and examine whether existing rules of international human rights law, especially those concerning non-State actors, provide any basis for such application.